PENGEMBANGAN SDM BERBASIS KOMPETENSI ANTARA PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA DI LINGKUNGAN PENDIDIKAN - Edward Gagah Purwana Taunay (Jurnal Ekonomi dan Bisnis Kontemporer, 2015)
Organisational culture will funtion optimally of organizational members have the same perception toward culture and strong participate in culture. The purpose of this research isto developed human resources in competency basic and analyze the influence of organisational culture and competency toward performance in education environmet. Keyword : competency, organisational culture, performance